2014
DOI: 10.1155/2014/547187
|View full text |Cite
|
Sign up to set email alerts
|

NGF Accelerates Cutaneous Wound Healing by Promoting the Migration of Dermal Fibroblasts via the PI3K/Akt-Rac1-JNK and ERK Pathways

Abstract: As a well-known neurotrophic factor, nerve growth factor (NGF) has also been extensively recognized for its acceleration of healing in cutaneous wounds in both animal models and randomized clinical trials. However, the underlying mechanisms accounting for the therapeutic effect of NGF on skin wounds are not fully understood. NGF treatment significantly accelerated the rate of wound healing by promoting wound reepithelialization, the formation of granulation tissue, and collagen production. To explore the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 45 publications
1
58
0
2
Order By: Relevance
“…Factor Induced Gene 4 (FIG4), a key plasma membrane protein with critical roles in phosphatidylinositol (3,4,5)-triphosphate (PI(3,4,5)P 3 or PIP 3 ) synthesis and neural differentiation (12), has also been established as a biomarker for reinnervation. Of particular relevance for reinnervation following cutaneous injury, nerve growth factor (NGF; key molecule in cell migration (13)) has also been shown to modulate gene expression associated with neural differentiation in neural-crest derived cells such as epidermal melanocytes (14) and Merkel cells (15) In our initial study examining the effects of ES on human cutaneous wound healing, we identified enhanced angiogenesis and re-epithelialisation in human cutaneous wounds (23).…”
Section: What Were the Ages/gender Of The 4 Participants Used For Thementioning
confidence: 99%
“…Factor Induced Gene 4 (FIG4), a key plasma membrane protein with critical roles in phosphatidylinositol (3,4,5)-triphosphate (PI(3,4,5)P 3 or PIP 3 ) synthesis and neural differentiation (12), has also been established as a biomarker for reinnervation. Of particular relevance for reinnervation following cutaneous injury, nerve growth factor (NGF; key molecule in cell migration (13)) has also been shown to modulate gene expression associated with neural differentiation in neural-crest derived cells such as epidermal melanocytes (14) and Merkel cells (15) In our initial study examining the effects of ES on human cutaneous wound healing, we identified enhanced angiogenesis and re-epithelialisation in human cutaneous wounds (23).…”
Section: What Were the Ages/gender Of The 4 Participants Used For Thementioning
confidence: 99%
“…The ovariectomized mice were kept until 8 to 10 weeks of age for further experiments. The two groups of mice were then anesthetized with isoflurane (1 -4%) in oxygen and shaved prior to the generation of a bilateral incision of approximately 1 cm in length, as described previously [18]. Photos of the incisions from the same mouse were taken at 0, 1, 3, 5, and 7 days following incision generation for comparison.…”
Section: Animal Modelmentioning
confidence: 99%
“…The extracellular signal-regulated kinase (Erk) and phosphatidylinositol 3-kinase (PI3-kinase) signaling pathways, which have been reported to be activated by basic fibroblast growth factor (bFGF), nerve growth factor (NGF), valproic acid, etc., have been reported to be crucial for cutaneous wound healing [18][19][20][21][22]. Furthermore, activation of the Erk signaling pathway has been reported in keratinocyte proliferation induced by the application of exogenous estrogen [23].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, at the protein level BDNF and both isoforms of TrkB are strongly localized in basal keratinocytes and in cells of vascular inner dermis in close association with fibrous periosteum, both at distal and proximal sites of bone formation. Indeed, the other neurotrophin NGF promotes cutaneous wound healing by inducing a fibroblast migration (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%